Granulomatous lesions and Mycobacterium avium subsp. paratuberculosis in portuguese wild boars (Sus scrofa) - Matos, Ana Cristina (2012)
Granulomatous lesions and Mycobacterium avium subsp. paratuberculosis in portuguese wild boars (Sus scrofa).